Cartographies of Identity in Caballos salvajes. - SANDMANN, SUSANA (Rocky Mountain Review of Language & Literature (1948-2833))
This article examines the construction of the landscape in the Argentine film Caballos salvajes (Piñeyro 1995) and proposes that, by instilling the images of Patagonia with a sense of place, this film creates a "geography of belonging." The emphasis on the landscape as place attempts to anchor national identity in the national territory as a way to resist the cultural condition of globalization: deterritorialization. To do so, the film relies on the well-known geographic antinomy Buenos Aires versus the interior, with which it awakens the chain of meanings that it evokes in the national public. Even though the film uses the codes and conventions of Hollywood genres such as the road movie and the Western to attract international audiences, it firmly anchors the resistance to globalization in the images of the interior of Argentina, in the place where, according to the film, the roots of an authentic national culture are still found. To encourage the engagement of graduate students in scholarly production, the Rocky Mountain Review is recognizing excellence among our graduate student membership by publishing two papers, first presented at the RMMLA conference, that won the Davis Award. Both papers are presented in their original versions: not subjected to peer-review but simply edited for publication. We hope that this feature will inspire graduate students in the humanities to pursue their scholarly efforts and to submit their work at our annual conference.